On the Study of the Scenes of Torment in the Art of People of Pazyryk Culture Based on Materials from Kurgan 11 of the Berel Graveyard in the Kazakh Altay - Bazarbayeva, G.А.; Jumabekova, G.S. (Археологія і давня історія України, 2021)
In this paper, we present the analysis of the scene
from a saddle cover found in kurgan 11 of Berel (4th—
3rd centuries BC). This material was first published in
the Povolzhskaya Arkheologiya journal (Алтынбеков и
др. 2019; Джумабекова, Базарбаева 2019). Here, we
provide new data based on the analysis of the informative
elements of the animal images and broaden the
range of the analogies.
In the archeology of the Early Iron Age of the eastern
part of Eurasia, materials from permafrost mounds
are of great importance. They allow to clarify in many
respects various elements of material culture of the
population living in the region. The state of preservation
of the contents of the tomb can be compared with
ethnographic exhibits. In 1998—1999 international
expedition of the Institute of Archeology. A. H. Margulan
under the leadership of Z. Samashev studied the
mound 11 cemetery Berel (4—3 centuries BC) in the
Kazakh Altai, which preserved the lens of permafrost.
The peculiarity of the excavations was that the contents
of the burial chamber were removed in separate
blocks for further study in the laboratory. Cabinet research
was conducted in the winter of 2000. Since then,
part of the material was stored in a freezer in the research
and restoration laboratory «Island of Crimea».
Under the leadership of K. Altynbekov, organic artifacts
were gradually restored and preserved. A recent
discovery by laboratory staff was the discovery of the
remains of a saddle cover embroidered with a scene of
torture by four ungulate predators. This material was
first published in 2019 in the journal «Volga Archeology
». This article provides materials that significantly
complement the above analysis. The range of analogies
has been expanded. In the interpretation of certain
zoomorphic images, emphasis is placed on ornamental
elements. In particular, stylized images of spiral curls
found in materials from monuments of Central Asia: in
the Altai, Tuva, Ordos were analyzed in detail.
The analyzed plot on the saddle cover from Berel is
close, but not identical to the drawings that have survived
as tattoos on the buried from Pazyryk, Ak-Alahi,
Verkh-Kaldzhin. The reception in the form of blackening of certain content elements in the transfer of images
of animals, both real and fantastic, attracts attention.
One of the favorite plots in the art of the Pazyriks is the
scene of torment, which conveys the traditional idea of
the cycle of life and death, rebirth through death. В археології раннього залізного віку східної частини Євразії велике значення мають матеріали з
курганів із мерзлотою. Саме вони дозволяють багато
в чому прояснити різноманітні елементи матеріальної культури населення, що мешкало у регіоні. Стан
збереженості вмісту внутрішньомогильної споруди
можна порівняти з етнографічними експонатами.
У 1998—1999 рр. міжнародна експедиція Інституту археології ім. А. Х. Маргулана під керівництвом
З. Самашева вивчала курган 11 могильника Берел
(IV—III ст. до н. е.) у Казахському Алтаї, в якому
збереглася лінза мерзлоти. Особливість розкопок по-
лягала в тому, що вміст поховальної камери виймався окремими блоками з метою подальшого вивчення у лабораторних умовах. Кабінетні дослідження
проводилися взимку 2000 р. З того часу частина матеріалу зберігалася у морозильній установці у науково-реставраційній лабораторії «Острів Крим». Під
керівництвом К. Алтинбекова артефакти з органіки
поступово реставрувались та консервувалися. Нещодавнім відкриттям співробітників лабораторії стало
виявлення залишків сідельного покриття з вишивкою, що містить сцену терзання чотирма хижаками
копитної тварини. Вперше цей матеріал було опубліковано у 2019 р. у журналі «Поволзька археологія». У цій статті наводяться матеріали, що суттєво
доповнюють викладений раніше аналіз. Розширено
коло аналогій. У трактуванні тих чи інших зооморфних образів, зроблено акценти на орнаментальних елементах. Зокрема, детально проаналізовано
стилізовані зображення спіралеподібних завитків,
що зустрічаються у матеріалах з пам’ятників Центральної Азії: на Алтаї, Туві, Ордосі.
Аналізований сюжет на сідельному покритті з
Берела близький, але не ідентичний малюнкам, що
збереглися як татуювання на похованих з Пазирика,
Ак-Алахі, Верх-Кальджіна. Привертає увагу прийом у вигляді зачорніння тих чи інших змістовних
елементів у передачі зображень тварин, як реальних, так і фантастичних. Один з улюблених сюжетів
у мистецтві пазирикців — сцена терзання, передає
традиційну для досліджуваної епохи ідею круговороту життя і смерті, відродження через смерть.